Protecting Research Participants While Reducing Regulatory Burdens - Lo, Bernard; Barnes, Mark (JAMA : the journal of the American Medical Association, 2011)
The Department of Health and Human Services has proposed sweeping revisions to the federal regulations for the protection of human research participants. The goal is to "enhance protection while simultaneously eliminating unreasonable burdens." Although the goal is admirable, some changes intended to remove unnecessary regulatory burdens may allow serious risks particularly to highly vulnerable participants. Lo and Barnes discuss major issues in the Advance Notice of Proposed Rule-Making--ensuring risk-based protections, institutional review board reviews of multisite studies, and informed consent.